Biohydrogen production from wood dust mahogany (Swietenia mahagony) by dark fermentation using Enterobacter aerogenes: Effect of ozone pretreatment time and pH. (2022) - Praptyana, I.R.; Budiyono,
Abstract: As a results of the large-scale exploitation of fossil energy, the availability of non-renewable energy sources as the main energy source has decreased dramatically in the last two decades. Biomass is a versatile renewable energy source. Wood dust mahogany is an agricultural waste and one of the most commonly found biomass in Indonesia that can be converted into biohydrogen by dark fermentation. Biohydrogen is one of the alternative energy sources that is claimed to be the cleanest and environmentally friendly. However, the lignin content causes the hydrolysis process and biohydrogen production run slowly. Therefore, ozone pretreatment is necessary to degrade lignin. The advantage of ozonation pretreatment is the reactivity of ozone and does not produce by-products. In this biohydrogen research the effect of pH and ozonation pretreatment time on characteristics of wood dust mahogany, biohydrogen formation rate and its kinetic will be studied. This research was conducted in 3 stages consisting of preparation stage, ozone pretreatment stage and biohydrogen fermentation stage. The variations of the ozone pretreatment observed factor are 3, 7, 11 for pH and 15, 45 min for ozonation time. Biohydrogen fermentation using Enterobacter aerogenes for 26 h will be the last stage. The biohydrogen gas was analyzed using water displacement method for its volumetric measurement every 2 h and used for kinetic study of biohydrogen production using modified Gompertz model. The results of experiment demonstrates that ozone pretreatment leaded to wood dust mahogany surface structure change and has a positive impact on increasing the rate of biohydrogen formation. Meanwhile, the best ozone pretreatment pH was at alkaline environment (pH 11). Ozone pretreatment gives a significant impact compared to biohydrogen production accumulation without pretreatment. It can increase the production until 68%. If we compare to the other pretreatment methods, biohydrogen production from lignocellulosic substrate with ozone pretreatment produce greater results up to 86.9%. The kinetic results using modified Gompertz model could be well fitted (R 2 0.981–0.995) to the experimental results.